KONSEP IDEALISME WARTAWAN DALAM INDEPENDENSI MEDIA MASSA - Anhar Fazri; Rahma Hidayati; Desi Maulida (SOURCE : Jurnal Ilmu Komunikasi, 2021)
Journalists are members of the press who play an important role in the delivery of information to the public. The important role of journalists will of course be greatly influenced by their idealistic attitudes to maintain a mindset that they think is right about the media work they do. The purpose of this study was to determine the concept of journalist idealism in the context of mass media independence. This study uses a qualitative method with a methodological approach and study approach. The informants in this study were journalists and informants related to the mass media. The results showed that technological developments and changing political conditions had a new influence on the social life of journalists themselves, especially in promoting a strong attitude of professionalism. The determination of principles by prioritizing journalistic ethics and unchanging idealism presents challenges for journalists. The mass media that moves by prioritizing the market mechanism or media capitalism will give a negative stigma to the journey of the mass media. Therefore, the mass media and journalists must be able to control themselves and the institutions so that they can run a press institution without any element of interest from certain parties.